Influence of the Level of Pedicle Subtraction Osteotomy on Pelvic Tilt Change in Adult Spinal Deformity. Issue 1 (April 2016) - Sebaaly, Amer; Kharrat, Khalil; Kreichati, Gaby; Rizkallah, Maroun
Background: Spine osteotomy is used for patients with rigid severe spinal deformity. Pedicle Subtraction Osteotomy (PSO) is performed by removing the posterior elements and both pedicles, removing a wedge from the vertebral body, and closure of the osteotomy by hinging on the anterior cortex. This technique is demanding and have very steep learning curve. We analyze the effect of the level of PSO on the change of pelvic tilt Methods: this is a retrospective study of 35 patients (mean age, 60.7 years; range, 45–81 years) undergoing thoracolumbar PSO at a single institution in the past 4 years. One patient underwent PSO at T11, two patient underwent PSO at L2, and 16 patients underwent PSO at L3 and 16 at the L4 level. Seventy percent of the patients had undergone at least one previous spine surgery in the region of the PSO. Results: the mean pelvic incidence in the cohort was 54.5. There was no change in the pelvic tilt between the preoperative and postoperative state (24.8 vs 22; p > 0.05). On the other hand, lumbar lordosis (26 vs 44), thoracic kyphosis (27 vs 38.8) and T1 pelvic angle (26.6 vs 14.7) had all significant improvement. Mean PSO resection was 35°. With subgroup analysis, mean pelvic tilt change -3.3° at the L3 level and -8.6 ° at the L4 level. Conclusions: The degree of PSO resection correlates greatly with spinopelvic parameters (lumbar lordosis, thoracic kyphosis, and T1PA). More importantly, PSO level impacts postoperative PT correction; L4 level PSO have shown a better correction of the pelvic tilt than L3 PSO.